Lifespan estimate for semilinear wave equation in Schwarzschild spacetime. (January 2020) - Lin, Yinhe; Lai, Ning-An; Ming, Sen
Abstract: In this paper we prove the blow-up result for small data Cauchy problem of semilinear wave equation in Schwarzschild spacetime with p ∈ [ 3 2, 2 ], without the assumption that the supports of the initial data should be far away from the black hole. What is more, we establish the upper bound of the lifespan estimate.